2013
DOI: 10.4028/www.scientific.net/amm.357-360.844
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of the Mechanical Properties of Jointed Rubber Wood Using Two Types of Adhesives

Abstract: Wood, a potentially good construction material in terms of sustainability, has less structural use now in India. Due to easy availability, low cost and good working quality there is a scope for the value addition of rubber wood in the Country. Finger jointing technology benefits high economic advantage by upgrading rubber wood. There is a dearth of information for the influence of adhesive on the mechanical properties of jointed rubber wood in India. This study was conducted to evaluate the effects of adhesive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
1
1
Order By: Relevance
“…9. In comparison to other finger-jointed wood products made of other wood species, it was found that the finger joint efficiency of FJOP obtained from this study was lower than that of the finger-jointed rubberwood product that was produced using the same finger profile and adhesive type (FE = 82.42% for σ//) (Nadir and Praveen 2013).…”
Section: Compression In Parallel Direction To the Fiber Testcontrasting
confidence: 64%
See 1 more Smart Citation
“…9. In comparison to other finger-jointed wood products made of other wood species, it was found that the finger joint efficiency of FJOP obtained from this study was lower than that of the finger-jointed rubberwood product that was produced using the same finger profile and adhesive type (FE = 82.42% for σ//) (Nadir and Praveen 2013).…”
Section: Compression In Parallel Direction To the Fiber Testcontrasting
confidence: 64%
“…The finger joint efficiency (FE) of oil palm wood (percentage of finger-jointed wood product to solid wood property ratio) obtained from this study was found to be very similar compared with that of rubberwood (FE was approximately 68.3%, MOR = 58.5 MPa), which was produced using the similar finger profile and adhesive type (Nadir and Praveen 2013). However, the MORF of FJOP was relatively low.…”
Section: Bending Testmentioning
confidence: 58%